Paternal attachment, negative life events, automatic thoughts and depressive symptoms in Malaysian adolescents - Yahya, Amira Najiha (2017)
Numerous studies documented the risk for depressive symptoms increases during adolescence. Thus it is imperative to examine factors related to its occurrence. The origins of depressive symptoms additionally have yet to be fully understood. Therefore, it is deemed necessary to identify the mechanism that triggers its occurrence in order to expand knowledge about the etiology of depressive symptoms amongst Malaysian adolescents. This cross-sectional study aimed to investigate the relationships between paternal attachment (i.e., secure, anxious fearful, responsiveness and approachability), negative life events (NLE) and depressive symptoms. In addition, automatic thoughts variable was tested as a mediator and sex as a moderator for these relationships. The sample comprised 1030 secondary school adolescents aged between 13 and 19 years (mean = 15.36) from the states of Pulau Pinang, Kelantan, Kuala Lumpur and Johor who were selected using probability proportional to size cluster sampling. The adolescents provided information by completing self-report measures on the study variables. Structural equation modeling was performed using AMOS to test the study hypothesized model. A measurement model was developed to validate the study measures before conducting structural model testing. The model revealed an excellent fit (χ2=372.558, df =103, χ2/ df =3.653, p <0.001; CFI = 0.968; GFI = 0.957; RMSEA = 0.05). Results indicated that secure and approachability attachments were negatively related to depressive symptoms, whereas attachment characterized by anxious fearful had a positive relation with depressive symptoms. Conversely, there were no direct relation between responsiveness and NLE to depressive symptoms. Findings from the mediational analyses found that automatic thoughts had indirect effects on the respective relationships of two attachment variables (i.e., anxious fearful and responsiveness) and NLE to depressive symptoms. Results from multi-group analyses showed support for model variance between male and female adolescents. Pathways from these attachment variables and NLE to automatic thoughts were found to be significantly different across sex. Sex differences also emerged in the relationship between automatic thoughts and depressive symptoms, along with the associations of each of the three attachment variables, specifically, secure, anxious fearful and approachability to depressive symptoms. Generally, the study showed that secure, anxious fearful and approachability attachments are the leading contributors for depressive symptoms in adolescents. Further, automatic thoughts were evidenced to contribute indirectly to the pathways that lead attachment variables and NLE to depressive symptoms. The study concludes that the ability of fathers to sustain secure and approachability attachments is clearly important to protect adolescents from experiencing depressive symptoms. Inversely, anxious fearful attachment predicted the development of depressive symptoms in adolescents. As such, high responsiveness and low anxious fearful attachments from fathers, experiencing less NLE, together with less automatic thoughts could essentially mollify the risk for depressive symptoms in adolescents. Concisely, the study inferred that adolescents who were securely attached, less anxious fearful and received great approachability from their fathers were more likely to experience less depressive symptoms. Findings from the present study clearly advance existing literature by providing a better framework for understanding the etiology of depressive symptoms in adolescents. Educators, practitioners and those working with or for adolescents may find information from the present study useful for designing various prevention and intervention programs related to adolescents’ psychological health and well-being.